2020
DOI: 10.1111/jocs.15133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different pulmonary valve reconstruction techniques during transannular repair of tetralogy of fallot

Abstract: Background: Transannular patch, which results in pulmonary insufficiency (PI), is usually required during repair of tetralogy of fallot (TOF). In this study, we compared three types of pulmonary valve reconstruction techniques during transannular repair of TOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Temur et al compared the results of ToF treatment with three methods: glutaraldehyde-treated autologous pericardial patch as monocusp, Nunn's bileaflet pulmonary valve reconstruction technique with pericardial patch and Nunn's bileaflet technique with expanded polytetrafluoroethylene membrane, however, with a small number of patients in particular groups. 22 Freedom from moderate to severe pulmonary insufficiency reported in this study were 73.3%, 100%, and 89.4% in particular groups, respectively; however, it decreased to 40%, 81.2%, and 73.7%, respectively, at the end of the follow-up period with a mean follow-up of 17.5 ± 13.0 months. Also, Kumar et al reported that in a group of 171 patients (25 were lost to follow-up) 42 have required replacement of their monocusp valves 10.1 ± 5.0 years after original monocusp insertion.…”
Section: Commentmentioning
confidence: 43%
“…Temur et al compared the results of ToF treatment with three methods: glutaraldehyde-treated autologous pericardial patch as monocusp, Nunn's bileaflet pulmonary valve reconstruction technique with pericardial patch and Nunn's bileaflet technique with expanded polytetrafluoroethylene membrane, however, with a small number of patients in particular groups. 22 Freedom from moderate to severe pulmonary insufficiency reported in this study were 73.3%, 100%, and 89.4% in particular groups, respectively; however, it decreased to 40%, 81.2%, and 73.7%, respectively, at the end of the follow-up period with a mean follow-up of 17.5 ± 13.0 months. Also, Kumar et al reported that in a group of 171 patients (25 were lost to follow-up) 42 have required replacement of their monocusp valves 10.1 ± 5.0 years after original monocusp insertion.…”
Section: Commentmentioning
confidence: 43%